1993
DOI: 10.1007/bf01213373
|View full text |Cite
|
Sign up to set email alerts
|

Renal ?-adrenergic receptors and genetic hypertension

Abstract: The hypothesis has been proposed that an increase in the number of renal alpha-adrenergic receptors may contribute to the pathogenesis of genetic hypertension. Herein we review recent findings regarding expression of renal alpha 1 (alpha 1a, alpha 1b)- and alpha 2 (alpha 2a, alpha 2b)-adrenergic subtypes and we provide an updated revision of the above-stated hypothesis. Enhancement in receptor number or in post-receptor components responsible for alpha 1- and alpha 2-adrenergic-mediated sodium reabsorption in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…It has been shown that CQ acts on venous α2B adrenergic receptors to produce constriction and increase venous blood return to the heart and also stimulates central α2A adrenergic receptors to produce a decrease in systemic vascular resistance (SVR) ( Gulati et al, 2020 ; Gulati et al, 2020 ) and thus it helps in increasing the cardiac output. Kidney tissues have abundant α-adrenergic receptors and their localization is primarily in renal arterioles, glomeruli and tubules of the renal cortex and medulla ( Jackson and Insel, 1993 ). They are involved in the regulation of renal blood flow, glomerular filtration rate, renin release and sodium re-absorption ( de Leeuw and Birkenhager, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CQ acts on venous α2B adrenergic receptors to produce constriction and increase venous blood return to the heart and also stimulates central α2A adrenergic receptors to produce a decrease in systemic vascular resistance (SVR) ( Gulati et al, 2020 ; Gulati et al, 2020 ) and thus it helps in increasing the cardiac output. Kidney tissues have abundant α-adrenergic receptors and their localization is primarily in renal arterioles, glomeruli and tubules of the renal cortex and medulla ( Jackson and Insel, 1993 ). They are involved in the regulation of renal blood flow, glomerular filtration rate, renin release and sodium re-absorption ( de Leeuw and Birkenhager, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Despite the great amount of research on the subject, the specific events that lead to the development of high blood pressure (BP) are not known. However, at the vascular level, 2 factors seem to be involved in the pathogenesis of this condition: (1) structural changes in blood vessel walls and (2) hypersensitivity of blood vessels to vasoconstrictor stimuli.…”
mentioning
confidence: 99%
“…5,6 The ARs in the kidney are expressed in arterial smooth muscles, tubule epithelial cells, and juxtaglomerular renin cells, where they reduce renal blood flow, increase reabsorption, and stimulate renin secretion, respectively. Although in vivo and in vitro pharmacological studies have revealed diverse effects of ARs in the kidney 5,[7][8][9][10][11][12] and the vasculature and nephron segments have different types of ARs, [13][14][15][16] the positional relationship of ARs to sympathetic nerve terminals and the pathways through which NE stimulates them remains unknown.…”
Section: Introductionmentioning
confidence: 99%